Model Revitalisasi Pengelolaan Pasar Tradisional - Febrianty, Dessy (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
Although aimed at improving the performance and quality of the market, in fact the traditional market revitalization program was not entirely successful. This is because the revitalization programs those have not been developed in the physical, economic and social aspects at the same time. That requires a revitalization model that can be used in an effort to revive and develop the traditional markets. Research conducted in Surakarta, Binjai and Manado aims to produce a revitalization model of traditional market management. Qualitative approach is used to elaborate the meanings associated modeling. The final results showed that not only the influenced of social capital in the process of revitalization, but also significantly influenced by human capital, institutional capital and economic capital which is a unity that can not be separated.